Polymer-grafted hollow mesoporous silica nanoparticles integrated with microneedle patches for glucose-responsive drug delivery - WANG, Yaping; CHENG, Songyue; HU, Wei; LIN, Xue; CAO, Cong; ZOU, Shufen; TONG, Zaizai; JIANG, Guohua; KONG, Xiangdong (Frontiers of materials science, 2021)
A glucose-mediated drug delivery system would be highly satisfactory for diabetes diagnosis since it can intelligently release drug based on blood glucose levels. Herein, a glucose-responsive drug delivery system by integrating glucose-responsive poly(3-acrylamidophenylboronic acid) (PAPBA) functionalized hollow mesoporous silica nanoparticles (HMSNs) with transcutaneous microneedles (MNs) has been designed. The grafted PAPBA serves as gatekeeper to prevent drug release from HMSNs at normoglycemic levels. In contrast, faster drug release is detected at a typical hyperglycemic level, which is due to the change of hydrophilicity of PAPBA at high glucose concentration. After transdermal administration to diabetic rats, an effective hypoglycemic effect is achieved compared with that of subcutaneous injection. These observations indicate that the designed glucose-responsive drug delivery system has a potential application in diabetes treatment.